The impacts of the COVID-19 pandemic on the education of people with disabilities in the State of Alagoas (Research, Society and Development, 2021)
This study the impacts of the COVID-19 pandemic on the education of people with disabilities in the State of Alagoas, from the application of an online questionnaire, being quantitative and descriptive in nature. The online questionnaire, developed in google forms, was organized in two directions: one specific for the Person with Disabilities and another for the family member or person responsible for the Person with Disabilities, if it was not possible to be answered by the Person with Disabilities. The questionnaire was made available through a link on social networks (Facebook, Instagram, Whatsapp) or via email to reach people with disabilities in the State of Alagoas, The survey was conducted from August 28 to October 31, 2020 with the support of 139 participants, 36 people with disabilities and 103 relatives or guardians of the Person with Disabilities who answered the people with disabilities due to the COVID-19 pandemic, because, although educational activities have continued remotely these, according to the participants, did not occur satisfactorily, bringing reflections about the process adopted by the institutions and the needs of inclusive and effective strategies of schooling in order to reduce inequalities in the pandemic scenario and beyond this. The specificities of people with disabilities add characteristics that need to be considered in the construction of an individual educational plan, but always from the perspective of the inclusion and interaction of these individuals in the school dynamics.